Eksplorasi Patogen dan Intensitas Penyakit Bercak Daun pada Bibit Kelapa Sawit Simalungun - Hutagalung, Padi Perjuangan; Noer, Zulheri (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Oil palm (Elaeis guineensis Jacq) is a national leading commodity that contributes greatly to the Indonesian economy. However, the nursery stage becomes a critical phase that is susceptible to disease attacks, especially leaf spots. This study aims to identify the types of pathogens that cause leaf spots, as well as measure the incidence and intensity of diseases in several oil palm nursery locations in Simalungun Regency. The research was carried out using a field survey method and laboratory identification using a purposive sampling approach in six nursery locations: PPKS, PTPN IV Bahjambi (pre-nursery and main-nursery), PTPN IV Belimbingan, PTPN IV Tinjowan, and community gardens in Silampuyang. Pathogen identification was carried out through macroscopic, microscopic, and Koch postulates tests. The results of the study showed that leaf spot disease in oil palm nurseries in Simalungun was caused by Curvularia sp. and Pestalotiopsis sp., with the highest attacks in PPKS (50% and 45%). Other locations such as PTPN IV and Silampuyang showed an intensity varying between 15% to 40% depending on the type of pathogen that predominates.